Edmodo as Technology-Based Formative Assessment: How it Enhances Reading Comprehension - Nuraini, Fani Indriya; Sodiq, Jafar; Prastikawati, Entika Fani (LPPM Universitas PGRI Semarang, 2025)
This study investigates the effectiveness of Edmodo as a technology-based formative assessment tool in enhancing students’ reading comprehension. Employing a quasi-experimental design, the research involved two groups of junior high school students: an experimental class and a control class, each consisting of 30 students. While the control class employed traditional formative assessment methods, which included direct question-and-answer sessions during face-to-face instruction, the experimental class integrated Edmodo as a platform for technology-based formative assessment. Reading comprehension tests, administered as pre-tests and post-tests, served as the primary data collection instrument. The data were analyzed using SPSS 23 for descriptive statistics, N-gain, and t-test to assess the impact of the intervention. Results revealed that the experimental class, which utilized Edmodo, demonstrated significantly higher improvements in reading comprehension compared to the control class. The N-gain analysis highlighted a substantial increase in the experimental group’s performance, indicating the effectiveness of Edmodo in supporting student engagement and understanding of reading materials. This study underscores the potential of technology-based formative assessments, particularly through platforms like Edmodo, in creating interactive, timely, and student-centered learning environments. By providing immediate feedback and fostering collaborative learning, Edmodo enhances students’ comprehension skills, thereby offering an innovative approach to formative assessment in English language teaching. These findings advocate for the integration of digital tools into assessment practices to improve learning outcomes in reading comprehension.